The Concept Of Amanah Metaphor In Accounting: Meaning, Guidelines, And Purposes - Dwi Sulistiani (Universitas Serang Raya, 2024)
This paper aims to construct Amanah's (trustful) metaphor in accounting related to meaning, guidelines, and purpose. This research is a qualitative research with an interpretive paradigm which is analyzed using content analysis. Data obtained from structured interviews with 40 IAI (Indonesian Accountant Assosiation) member, the Holy Qur'an, Hadith, and other literature. The research results are in the form of the metaphorical concept of Amanah, which is interpreted by a human perspective in perceiving his duties as God's representative in the world. Accounting guidelines based on the metaphor of Amanah concept must be based on strong Aqidah, based on good morals, a responsibility to society and the Ummah, based on legal, financial processes, and behavioral aspects of each of their actions. Besides, it also purpose at hisful amwal, the existence of al kitabah, assisting decision making, calculating business zakat, determining and calculating profit sharing for the unionized party. These concept will change accountants' behavior to be more trustworthy and not materialistic because all of their work is intended only to get the pleasure of Allah.